2017
DOI: 10.3389/fonc.2017.00243
|View full text |Cite
|
Sign up to set email alerts
|

Metformin: A Bridge between Diabetes and Prostate Cancer

Abstract: Prostate cancer (PCa) has become the most frequent type of cancer in men. Recent data suggest that diabetic patients taking metformin have a lower incidence of certain cancer, including PCa. Metformin is the most common drug used in type II diabetes mellitus; its use has been shown to lower the incidence of several cancers, although there are ambiguous data about the anticancer activity of metformin. A large number of studies examined the potential antineoplastic mechanism of metformin although it is not still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 78 publications
1
28
0
Order By: Relevance
“…The role of metformin as an anti-tumor agent is wellestablished in many types of cancer including prostate cancer (23)(24)(25). Metformin has antineoplastic effects such as adenosine monophosphate-activated protein kinase (AMPK)-dependent suppression of androgen signaling pathway, and alterations of insulin-like growth factor-1 (IGF-1) signaling pathways that cause the growth and proliferation of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The role of metformin as an anti-tumor agent is wellestablished in many types of cancer including prostate cancer (23)(24)(25). Metformin has antineoplastic effects such as adenosine monophosphate-activated protein kinase (AMPK)-dependent suppression of androgen signaling pathway, and alterations of insulin-like growth factor-1 (IGF-1) signaling pathways that cause the growth and proliferation of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In the TRAMP mouse model, metformin inhibited prostate cancer progression through inflammatory responses . These findings suggest that inhibition of prostate cancer progression by metformin might be mostly mediated by inflammation, whereas several reports showed that the mechanism was mediated by other pathways, including 5’ adenosine monophosphate‐activated protein kinase activation . Metformin has been shown to alter the tumor immune microenvironment, including macrophages, and suppress disease progression in obese pancreatic and breast cancer mouse models .…”
mentioning
confidence: 92%
“…Pre‐treatment of PC3 cells with the mTOR inhibitor rapamycin was shown to inhibit the accumulation of HIF1α . Further studies have shown that metformin inhibits mTOR via both AMPK‐dependent and ‐independent pathways ; therefore, we investigated whether metformin might reduce the expression of HIF1α in PC3 cells via inhibition of mTOR. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%